DINAMIKA PRODUKSI DAN KONSUMSI ROKOK INDONESIA SEBAGAI PENYEBAB IMPOR TEMBAKAU DARI BRASIL - Fadlillah, Fandhy Maulana; Iskandar, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Indonesia conducts international trade to meet its national needs for a commodity, namely tobacco. Indonesia's tobacco production is not enough to meet its needs. This need is influenced by the high number of smokers. Therefore, Indonesia imports from various countries, one of which is Brazil. This research is a qualitative study with secondary data collection taken from journals, news, and official websites. This thesis in accordance with the theme uses the theory of international trade put forward by Hecsker-Ohlin which assumes that there are two countries (Country 1 and Country 2), two commodities (commodity X and commodity Y), and two factors of production (labor and capital). Indonesia's tobacco production continues to increase, which is around 200 thousand tons, but Indonesia's tobacco needs reach 300 thousand tons, the magnitude of demand does not escape the high consumption of cigarettes around 34.5 percent. Therefore, Indonesia imports tobacco from Brazil to meet its national needs. Thus, the volume of Brazilian tobacco imports continues to increase despite fluctuations every year. Keywords: Brazil, Import, Indonesia, Consumption, Production, and Tobacco